Assessment of Nutritional Status of the A/L Students Using BMI - Sulosana, P.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Under nutrition and infectious diseases were traditionally considered as major problems in the developing country. But South Asian populations suffer with obesity associated complications at a lower Body Mass Index (BMI). Data on prevalence of obesity or underweight among A/L school students were not published. The present study was designed to determine the prevalence of overweight and underweight among A/L students of J/ Kaithady Muthukumarasaami Maha Vidyalayam (J/M.M.V). A total of 27 students (male:female ratio 1:2) of the Grade 12 and Grade 13 students (aged 17-18) of J/M.M.V were participated in this study. The mean age was similar in males and females. Standard procedures and equipments were used to measure the height and weight. BMI (Kg/m2) was calculated using height and weight. The study was conducted after obtained written consent from the school principal and the children themselves. The mean BMI is 18.275 +3.06 Kg/m2 in males and 20.30±2.83 Kg/m2. When classified according to the BMI cutoff values for Asians, among the males 55.56% were normal weight and 44.44% were underweight. Of the females 50% were underweight, 44.44% were normal weight and 5.56% were overweight. None were found to be obese. Therefore more attention should be taken to increase the body weight of who are in underweight, and obesity based complications were not identified in this study.
Keywords: BMI; Underweight; Overweight